Estimates of uncertainty around Australian budget forecasts - Clark, John (OECD Publishing, 2014)
In this article, past forecast errors are used to construct confidence intervals around Australian Government Budget forecasts of key economic and fiscal variables. These confidence intervals provide an indication of the extent of uncertainty around the point estimate forecasts presented in the Budget. JEL classification numbers: E17, H68. Keywords: Confidence intervals, forecast errors, government budget, nominal GDP, real GDP, treasury, uncertainty